Chloride–hydrogen antiporters ClC‐3 and ClC‐5 drive osteoblast mineralization and regulate fine‐structure bone patterning in vitro. Issue 11 (24th November 2015) - Larrouture, Quitterie C.; Nelson, Deborah J.; Robinson, Lisa J.; Liu, Li; Tourkova, Irina; Schlesinger, Paul H.; Blair, Harry C.
Abstract: Osteoblasts form an epithelium‐like layer with tight junctions separating bone matrix from extracellular fluid. During mineral deposition, calcium and phosphate precipitation in hydroxyapatite liberates 0.8 mole of H + per mole Ca +2 . Thus, acid export is needed for mineral formation. We examined ion transport supporting osteoblast vectorial mineral deposition. Previously we established that Na/H exchangers 1 and 6 are highly expressed at secretory osteoblast basolateral surfaces and neutralize massive acid loads. The Na/H exchanger regulatory factor‐1 (NHERF1), a pdz‐organizing protein, occurs at mineralizing osteoblast basolateral surfaces. We hypothesized that high‐capacity proton transport from matrix into osteoblast cytosol must exist to support acid transcytosis for mineral deposition. Gene screening in mineralizing osteoblasts showed dramatic expression of chloride–proton antiporters ClC‐3 and ClC‐5. Antibody localization showed that ClC‐3 and ClC‐5 occur at the apical secretory surface facing the bone matrix and in membranes of buried osteocytes. Surprisingly, the Clcn3 −/− mouse has only mildly disordered mineralization. However, Clcn3 −/− osteoblasts have large compensatory increases in ClC‐5 expression. Clcn3 −/− osteoblasts mineralize in vitro in a striking and novel trabecular pattern; wild‐type osteoblasts form bone nodules. In mesenchymal stem cells from Clcn3 −/− mice, lentiviral ClC‐5 shRNA created Clcn3 −/−, ClC‐5 knockdown cells, validated by western blot and PCR. Osteoblasts from these cells produced no mineral under conditions where wild‐type or Clcn3 −/− cells mineralize well. We conclude that regulated acid export, mediated by chloride–proton exchange, is essential to drive normal bone mineralization, and that CLC transporters also regulate fine patterning of bone. Abstract : We studied the hypothesis that H + transcytosis of epithelioid osteoblasts drives mineralization. Candidate genes were identified by cRNA screening with PCR, western blot, and in situ analysis identifying ClC‐3 and ClC‐5. Eliminating expression of both CLCs created cells that do not mineralize in vitro, and also revealed that ClC‐5 mediates fine patterning of bone production.